Comparative evaluation of diode laser ablation and surgical stripping technique for gingival depigmentation: A clinical and immunohistochemical study - Bakutra, Gaurav; Shankarapillai, Rajesh; Mathur, Lalit; Manohar, Balaji (International Journal of Health Sciences, 2017)
Introduction: There are various treatment modalities to remove the black patches of melanin pigmentation. The aim of the study is to clinically compare the diode laser ablation and surgical stripping technique for gingival depigmentation and to evaluate their effect on the histological changes in melanocyte activity. Materials and Methods: A total of 40 sites of 20 patients with bilateral melanin hyperpigmentation were treated with the surgical stripping and diode laser ablation technique. Change in Hedin index score, change in area of pigmentation using image analyzing software, pain perception, patient preference of treatment were recorded. All 40 sites were selected for immunohistochemical analysis using HMB-45 immunohistochemical marker. Results: At 12 months post-operative visit, in all sites, repigmentation was observed with different grades of Hedin index. Paired t-test, analysis of variance, and Chi-square tests were used for statistical analysis. Repigmentation in surgical stripping is significantly lesser compared to laser ablation. Lesser numbers of melanocytes were found on immunohistological examination at 12 months postoperatively. Comparison for patient preference and pain indices give statistically signifi cant values for diode laser techniques. Conclusion: Gingival hyperpigmentation is effectively managed by diode laser ablation technique and surgical stripping method. In this study, surgical stripping technique found to be better compared to diode laser ablation.